1989
DOI: 10.1111/j.1365-2621.1989.tb08578.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Vanillin by Fababean Proteins

Abstract: Binding of vanillin by fababean protein micellar mass (PMM) in water suspensions was investigated.Free vanillin was determined by HPLC and data were evaluated by the Klotz equation. Increasing vanillin and PMM concentrations increased the percentage of total vanillin bound to protein. Binding capacities of heat-treated (denatured) PMM were higher than that of untreated (native) PMM. Binding forces between vanillin and PMM were weak, and the number of binding sites increased when PMM was denatured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Increasing protein concentrations increased the percentage of total flavour bound . Land found that a decrease in percentage of flavour in the headspace was enhanced with an increase of the percentage of added proteins, irrespective of the types of proteins and flavours involved.…”
Section: Flavour‐food Matrix Interaction and Flavour Perceptionmentioning
confidence: 86%
See 2 more Smart Citations
“…Increasing protein concentrations increased the percentage of total flavour bound . Land found that a decrease in percentage of flavour in the headspace was enhanced with an increase of the percentage of added proteins, irrespective of the types of proteins and flavours involved.…”
Section: Flavour‐food Matrix Interaction and Flavour Perceptionmentioning
confidence: 86%
“…Soy proteins have been the most popular plant proteins used in flavour binding studies due to the presence of beany or grassy off‐flavours from lipoxygenase‐catalysed oxidation of unsaturated fatty acids . Pulse proteins are rarely studied; only pea protein and fababean protein have been evaluated. There have been no data reported for canola protein.…”
Section: Flavour‐food Matrix Interaction and Flavour Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other equilibrium techniques include liquid–liquid partitioning (Spector and others 1969; Spector 1975; Damodaran and Kinsella 1980b) and radioactivity counting (King and Solms 1979). For a few hardly volatile and water‐soluble flavor compounds, such as vanillin or benzaldehyde, HPLC methods have been developed to determine the free flavor after equilibration with the protein (Ng and others 1989a; McNeill and Schmidt 1993; Andriot and others 1999; Li and others 2000; Chobpattana and others 2002). However, several disadvantages are associated with equilibrium methods, such as long equilibration times and thus the possible degradation of the volatiles during this period.…”
Section: Analysis Of Flavor Binding By Proteinsmentioning
confidence: 99%
“…In the area of protein–flavor interactions, studies have been conducted mainly with milk proteins (Andriot and others 2000; Lübke and others 2002) and soy proteins (Damodaran and Kinsella 1981a; Li and others 2000), but also with a range of other food proteins, such as fababean protein (Ng and others 1989a, 1989b; Semenova and others 2002a), pea protein (Dumont and Land 1986), ovalbumin (Maier 1970; Ebeler and others 1988), fish actomyosin (Damodaran and Kinsella 1983), and myoglobin (Gianelli and others 2005). The studies on milk proteins are of great importance because milk proteins are utilized in numerous food products, including dairy products, bakery and confectionary products, and meat products (Mulvihill 1992).…”
Section: Introductionmentioning
confidence: 99%